Pelatihan Pengenalan Aplikasi Pembelajaran Edmodo bagi Mahasiswa Universitas Kanjuruhan Malang - Siti Mafulah; Trisno Tunggal Rahayu Wilujeng (Direktorat Penelitian dan Pengabdian kepada Masyarakat (DPPM), 2018)
In accordance with the vision of Universitas Kanjuruhan Malang as excellent campus in 2025 and excellent in education field in 2020, it is obviously important to do some actions. One of the ways is improving education quality through e-learning. The aims of this community service are 1) giving knowledge what kinds of application which can be applied in teaching learning process, 2) training the students in making Edmodo account, 3)knowing the students responses toward the use of Edmodo in teaching learning process. Method used in this activity is training. The steps were 1) introduced application that can be alternative media in teaching learning process, 2) introduced Edmodo as media, 3)workshop in making and joining group class, 4) simulation the use of Edmodo in small class and 5) evaluation. The finding of this activity was 85% students having good sense in applying Edmodo at class and Emodo is ready to be applied in class.